2020
DOI: 10.1111/jfpp.14420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of red pitaya (Hylocereus polyrhizus)peel powder as a fat replacer in ice cream

Abstract: This research aimed to characterize and apply a fiber obtained from a fruit residue as a fat substitute in ice creams. The by‐product of the processing of red pitaya pulp dried at low temperature proved to be a source of dietary fiber, with high soluble fiber content, and to have suitable technological properties, which is indicative of its potential as a fat replacer in foods, besides containing antioxidant properties. The addition of the fiber into strawberry ice cream improved overrun and rheological behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 42 publications
2
32
0
3
Order By: Relevance
“…In terms of the profitability of the product, overrun is important. Overrun seems to be an air mixing factor, which is an important predictor of ice cream volume and structural growth (Utpott et al, 2020).…”
Section: Effect Of Jamun Pomace Powder Incorporation On Overrun Of mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the profitability of the product, overrun is important. Overrun seems to be an air mixing factor, which is an important predictor of ice cream volume and structural growth (Utpott et al, 2020).…”
Section: Effect Of Jamun Pomace Powder Incorporation On Overrun Of mentioning
confidence: 99%
“…The higher amount of fiber in the added powder causes increased fiber content in ice cream. (Crizel et al, 2004;Gabbi et al, 2017;Goraya & Bajwa, 2015;Utpott et al, 2020) found that the fiber content increased with the addition of ginger powder, orange powder, amla, and pitaya fiber powder, respectively. F I G U R E 2 Effect of incorporated jamun pomace powder on the melting rate of ice cream F I G U R E 3 Effect of incorporated jamun pomace powder on the sensory properties of ice cream…”
Section: Effect Of Jamun Pomace Incorporation On the Fibers Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, before and after whipping, samples were allowed to be gently transferred into a flat Pyrex Petri dish (24 ml) of a known weight and weighed. The overrun percentage was determined using the following Equation (2): (Utpott et al., 2020). %Overrun=M1M2M1×100…”
Section: Methodsmentioning
confidence: 99%
“…3 Therefore, plants rich in betalains are not only regarded as valuable foods worldwide 4 but also have wide potential for use in food chemistry and technology. 5 , 6 Increasingly, attention is also paid to the valuable health-promoting properties of betalains. 7 In vitro studies as well as animal models in vivo showed promising perspectives in the use of betalain antioxidant and anti-inflammatory properties in the case of chronic inflammation, liver diseases, 8 arthritis, 9 and even with diseases associated with cancer (e.g., skin, lung, liver, colorectal cancers).…”
Section: Introductionmentioning
confidence: 99%